KUALITAS PELAYANAN STASIUN PENGISIAN BAHAN BAKAR UMUM PANRENG KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Karmila Yusuf; Kamaruddin Sellang; Hariyanti Hamid (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
This study aims to determine the quality of service affect customer satisfaction at Panreng SPBU District Baranti Sidenreng Rappang District and to find out which of the quality of services which include physical evidence, reliability, assurance, responsiveness, and empathy that have a dominant influence on customer satisfaction at Panreng SPBU Baranti District, Sidenreng Rappang Regency. The approach of the research method used in this research is a quantitative descriptive approach. The population in this study is customers who buy fuel oil at Panreng gas station, which is estimated that there are 250 buyers a day. The sample technique used is Random Sampling using the Slovin formula to produce 71 samples. Data collection techniques carried out in this study were observation, questionnaires, documentation, and literature study. The collected data is then processed and analyzed using quantitative descriptive analysis techniques with the help of descriptive statistics using SPSS 21.0 and Likert Scale. From the results of the study and discussion of the overall value shows that: (1) the quality of service affects customer satisfaction, declared significant / significant with a percentage of 55.1% obtained from the correlation coefficient in the model summary table. (2) the service quality factor which has the highest influence is the responsiveness indicator factor with a percentage of 74% obtained from the results of the questionnaire accumulation.